Reformist Attempts of Tammam Hassan in the Book Named “Meaning and Basis of Arabic Words” Reviewing the Correlation of Symbols’ Theory - Issa Motaqizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2019)
During the recent years, many studies have been conducted on the reformist attempts, and some scientists have played a key role in this field. One of these scientists is Tammam Hassan who has presented his reformist opinion in his popular book named “Meaning and Basis of Arabic Words”. In the fifth chapter of this book, Tammam Hassan has explained about vocabulary and spiritual symbols and role in understanding the meaning. Moreover, he considers eight vocabulary symbols and nine spiritual symbols and explains the effect of each of them in understanding the meaning. Introducing correlation of symbols’ theory, this article aims to investigate the dimensions of this theory and review the effect of this theory in understanding the meaning. Results of research show that this theory is capable to review different texts and allow researchers to have comprehensive view toward text and get the meaning of that by vocabulary and spiritual symbols.